Regional Economic Outlook : Sub-Saharan Africa - Fall 2006-Supplement. - Unspecified (International Monetary Fund, Ebrary, Incorporated [distributor], 2006)
Provides a broad synopsis of recent economic developments in the Middle East and Central Asia region, highlighting common trends and policies among countries in the region, and reviewing prospects and policies for the coming year. Includes a statistical appendix.